2020
DOI: 10.3389/fpsyt.2020.00769
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy in Common Dementias—Current Status and Perspectives

Abstract: Dementia occurs mainly in the elderly and is associated with cognitive decline and impairment of activities of daily living. The most common forms of dementia are Alzheimer's disease (AD), vascular dementia (VD), dementia with Lewy bodies (DLB), and frontotemporal dementia (FTD). To date, there are no causal options for therapy, but drug and non-drug treatments can positively modulate the course of the disease. Valid biomarkers are needed for the earliest possible and reliable diagnosis, but so far, such bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 80 publications
(185 reference statements)
1
33
0
Order By: Relevance
“…( Irwin et al, 2015 ) Indeed, while some frontotemporal dementia (FTD) clinical syndromes have group-level statistical associations with one of these proteinopathies, the majority of FTD syndromes do not reliably predict pathology. ( Irwin et al, 2015 , Gorno-Tempini et al, 2011 , Höglinger et al, 2017 , Giannini et al, 2019 , Irwin et al, 2018 , Perry et al, 2017 , Spinelli et al, 2017 ) Moreover, while various degenerative processes can be detected using structural, ( McKiernan and O’Brien, 2017 , McMillan et al, 2014 , Rohrer et al, 2009 , Whitwell et al, 2005 , Whitwell et al, 2015 , Perry et al, 2017 ), diffusion, ( McMillan et al, 2014 , Whitwell et al, 2010 , Illán-Gala et al, 2019 ), and spectroscopic MRI, ( Maul et al, 2020 , Murley et al, 20202020 ), as well as PET, ( Kim et al, 2019 , Whitwell et al, 2020 ); there is currently no method to directly sensitize traditional MRI, or any other in vivo imaging technology, including molecular imaging, to the specific protein inclusions or pathological features that would allow in vivo discrimination of patients with tau and/or TDP-43 inclusions in FTLD. In this report, we explore the novel combination of histopathology and T 2 *-weighted (T2*w) ex vivo 7 T MRI for the purpose of developing a more reliable, data-driven approach to diagnosis of pathology in FTLD spectrum disorders.…”
Section: Introductionmentioning
confidence: 99%
“…( Irwin et al, 2015 ) Indeed, while some frontotemporal dementia (FTD) clinical syndromes have group-level statistical associations with one of these proteinopathies, the majority of FTD syndromes do not reliably predict pathology. ( Irwin et al, 2015 , Gorno-Tempini et al, 2011 , Höglinger et al, 2017 , Giannini et al, 2019 , Irwin et al, 2018 , Perry et al, 2017 , Spinelli et al, 2017 ) Moreover, while various degenerative processes can be detected using structural, ( McKiernan and O’Brien, 2017 , McMillan et al, 2014 , Rohrer et al, 2009 , Whitwell et al, 2005 , Whitwell et al, 2015 , Perry et al, 2017 ), diffusion, ( McMillan et al, 2014 , Whitwell et al, 2010 , Illán-Gala et al, 2019 ), and spectroscopic MRI, ( Maul et al, 2020 , Murley et al, 20202020 ), as well as PET, ( Kim et al, 2019 , Whitwell et al, 2020 ); there is currently no method to directly sensitize traditional MRI, or any other in vivo imaging technology, including molecular imaging, to the specific protein inclusions or pathological features that would allow in vivo discrimination of patients with tau and/or TDP-43 inclusions in FTLD. In this report, we explore the novel combination of histopathology and T 2 *-weighted (T2*w) ex vivo 7 T MRI for the purpose of developing a more reliable, data-driven approach to diagnosis of pathology in FTLD spectrum disorders.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, although the MRI proton magnetic resonance spectroscopy technique - which assesses brain metabolites such as N-acetylaspartate (Naa), creatine (Cr), and myo-inositol (mI) - shows differences between groups of patients with and without AD, it still has many limitations and technique heterogeneity as to be applied in clinical practice as a marker of the disease. The main findings of the technique are a decrease in NAA and NAA/Cr ratio and an increase in mI and mI/Cr ratio 100 .…”
Section: Clinical Characterizationmentioning
confidence: 99%
“…Since changes in metabolism precede any structural changes in AD, MRS may appear to be an ideal technique for AD diagnosis. A recent review of MRS in common dementias has found decreased N-acetylaspartate (NAA) in posterior cingulate cortex, hippocampus, temporal, and parietal lobes in patients with AD [ 42 ]. Increased myo-inositol (mIns) and total choline levels, relative to total creatine (tCr), are also observed in the posterior cingulate cortex [ 42 ].…”
Section: Imaging Techniques In Current Clinical Practicementioning
confidence: 99%
“…A recent review of MRS in common dementias has found decreased N-acetylaspartate (NAA) in posterior cingulate cortex, hippocampus, temporal, and parietal lobes in patients with AD [ 42 ]. Increased myo-inositol (mIns) and total choline levels, relative to total creatine (tCr), are also observed in the posterior cingulate cortex [ 42 ]. However, the utility of MRS in prediction or differential diagnosis of AD has been hampered by a number of technical issues.…”
Section: Imaging Techniques In Current Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation